Navigating the VUCA in international student recruitment: response strategies from a private education institution’s perspective in Singapore - Peh, Weijie Vincent (2024)
We are living in an unprecedented VUCA world. Global events such as the COVID-19 pandemic, the geopolitical tensions between superpowers like the U.S. and China, the issues surrounding the South China Sea, the ongoing war between Russia and Ukraine, and the threat of more tensions escalating in the South China Sea, the Korean peninsula, and the Taiwan straits, etc, are all reminders that the world is undergoing rapid changes. What happens next is seemingly unpredictable and our future has never been more uncertain. As witnessed, some of the global events like the COVID-19 have sent shockwaves throughout the world, with International Business and trade heavily impacted, as well as putting a halt to the dreams of many International Students who wished to study abroad. Without the revenue streams from International Students, many education institutions globally have ended up in severe financial losses, and a massive number of jobs have been lost. Given that some recovery may have been achieved as we hopefully approach the end to the pandemic and its aftermath, more understanding is needed to ensure we recapture the interest of International Students and infuse more knowledge into coping with the VUCA affecting International Student Recruitment from the perspective of education institutions. The aim of this study examines the impact of VUCA on International Student Recruitment and propose strategies to cope with the challenges of VUCA that was imposed on International Student Recruitment from a perspective from a Private Education Institution, PSB Academy. This is done through a qualitative research approach by collecting data from International Student Recruitment Staffs working in PSB Academy. The study revealed the importance of Student Recruitment Agents and their role in mitigating many aspects of VUCA. Moreover, the findings also emphasised a need for restructuring of the sales and marketing team with the adoption of specialised and dedicated personnels into the team to enhance efficiency and create more focus for the sales team, such as local marketers and administrative support staff. Finally, the study concludes by proposing recommendations in line with the findings to optimise International Student Recruitment efforts and results in the VUCA landscape. This study contributes to a gap in literature surrounding International Student Recruitment and Marketing, add on to the understanding of VUCA in the International Student Recruitment landscape and provides practical insights for Private Education Institutions seeking to enhance their International Student Recruitment efforts.